Refractory Asthma : An Overview - Hasan, AMS; Hossain, MM; Mia, MSA; Mahmood, Iftekhar (TAJ: Journal of Teachers Association, 2011)
Patients whose asthma is not adequately controlled despite treatment pose a major clinical challenge and it is an important health care problem. It carries several names; each one points to an aspect of the disease. Chronic severe asthma, steroid-dependent asthma, steroid-resistant asthma, difficult-to-control asthma and refractory asthma are some of these terminologies. Patients with severe refractory disease often require regular oral corticosteroid with an increased risk of steroid-related adverse events. Alternatively, immunomodulatory and biologic therapies may be considered, but they show wide variation in efficacy across studies, thus limiting their generalization. Managing asthma that is refractory to standard treatment requires a systematic approach to evaluate adherence, ensure a correct diagnosis, identify coexisting disorders and trigger factors. In future phenotyping of patients with severe refractory asthma will also become an important element of this systematic approach. TAJ 2011; 24(1): 57-61